Implementation of Picture Card Media in Improving the Early Reading Ability of Children Aged 4-5 Years at (Paud) Raudhatus Sholihin - Khoirun nisa’; Mediyana; Dewi Pusparini (STIT Attaqwa, 2025)
This study aims to improve the early reading skills of children aged 4–5 years through the use of picture cards in Raudhatus Sholihin Early Childhood Education (PAUD). The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the application of picture cards can make it easier for children to recognize letters and vocabulary in a more interesting and appropriate way for children. This media successfully fosters interest in learning, makes the learning process more interactive, and helps children understand reading by associating letter symbols with images. In addition, teachers can also be more creative in designing fun learning activities so that the classroom atmosphere becomes more lively. Thus, the use of picture cards has proven effective as an alternative method for early reading learning in PAUD institutions, especially to support children's language development at an early age.